The implementation of multicultural education in German language learning - Wilma Akihary; Patrresia S Apituley (Journal of Education and Learning (EduLearn), 2019)
Multicultural education in a diverse cultural society is one of the important aspects to be addressed in order that it is not viewed as a threat in the current era of education 4.0. This researchaims at examining the implementation of multicultural education in German language learning, especially in the Aufbaustufe A2 course. The samples of this research were second semester students of class A in the Study Program of German Language Educationwith the total of 20 students. The instruments used in this research were questionnaires, interviews and document review. The data of the results of the questionnaire, interviews, and document review were analyzed by using descriptive statistics. The results of this research show that students are aware of their existence and also the existence of other students who have different cultural backgrounds. In addition, they respect their own culture even though they are also open to learning and understanding German culture.